Super-modified : the Behance book of creative work - Behance (Berlin : Gestalten, 2015)
Presenting a selection of trailblazing creativity from around the globe tightly curated by the Behance team, Super-Modified takes you inside the trends driving today's most exciting art and design. For example, the book looks at how a humble material such as felt is currently experiencing a renaissance in office spaces, furniture, and character design; how computer algorithms are being used to generate an infinite variety of breathtaking abstract shapes; how a focus on recycled design is making everything from discarded aluminum cans to shipping containers fair game for reinvention; and how the grand, cinematic visions of traditional architecture are finding their way into interior spaces. And that's just a small sample of the themes explored within. Behance's first book is comprised of 18 chapters, each of which represents a different facet of "super-modified" creative work. From innovative approaches to traditional crafts to wildly unexpected uses of new technologies, it tracks how classic approaches to art and design are being subverted, blurred, and reinvented by a remarkable group of emerging creatives. Featuring outstanding graphic design, photography, fashion, architecture, and illustration, Super-Modified surveys the landscape of global creativity and offers insight into what's coming next.
Keywords: Art and the Internet; Art and computers